(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
The advent of online language learning platforms has revolutionized language acquisition, particularly for English as a Second Language (ESL) learners. With the increasing prevalence of digital tools in education, these platforms offer flexible, interactive, and accessible means of learning.